Edukasi Tiga Ancaman Dasar Kesehatan Reproduksi Remaja (TRIAD KRR) Kepada Siswa SMA Se-Kab Sumbawa - Fitri Setianingsh; Desy Fadillah Adina Putri; Nurlaila Agustikawati (Pusat Riset dan Inovasi Nasional, 2022)
ABSTRACT This community service activity is carried out with the aim of increasing the understanding and awareness of high school students about the Three Basic Threats (TRIAD KRR) which includes sexuality, HIV/AIDS, and NAFZA as well as improving reproductive health in adolescents. The activity is carried out through the provision of health education with the technique of providing information or education about TRIAD KRR which consists of three materials, namely sexuality, HIV/AIDS and NAFZA. The material is given using power point media. The activity was carried out online (online) through the Zoom application and was attended by 31 participants from several high schools throughout the Sumbawa Regency. From the educational activities that have been carried out, students are enthusiastic in listening, asking questions and discussing, and the impact of this education is that students get an increase in students' understanding and awareness about the dangers of the Three Basic Threats (TRIAD KRR) which includes sexuality, HIV/AIDS, and NAFZA. improve their reproductive health by limiting association and doing lots of positive activities, this can be seen from the statements of the students during discussions and the speakers asking questions.